Almost cosympletic statistical manifolds - Erken, İrem Küpeli; Murathan, Cengizhan; Yazla, Aziz (Natl Inquiry Services Centre Pty Ltd, 2020)
This paper is a study of almost contact statistical manifolds. Especially this study is focused on almost cosymplectic statistical manifolds. We obtained basic properties of such manifolds. A characterization theorem and a corollary for the almost cosymplectic statistical manifold with Kaehler leaves are proved. We also study curvature properties of an almost cosymplectic statistical manifold. Moreover, examples are constructed.
Keywords: Primary; Secondary; Almost contact manifold; statistical manifold; conjugate connection Kaehler statistical manifold; Sasakian statistical manifold; Kenmotsu statistical manifold